EXPERIENCES OF THE ELDERLY IN SELF-MANAGEMENT OF JOINT PAIN IN THE BENCAH VILLAGE AREA - Suci Anggia Ervina; Indah Permata Sari (Poltekkes Kemenkes Jakarta III, 2026)
Joint pain is a health problem often experienced by the elderly due to degenerative processes and their impact on physical function, psychological condition, and daily activities. The success of joint pain management depends not only on medical therapy but also on the elderly’s ability to perform self-management. This study aims to explore the experiences of the elderly in self-managing joint pain in the Bencah Village area in 2025. This study employed a qualitative method with a phenomenological approach. Informants were selected using a purposive sampling technique involving four participants with the criteria of being elderly aged ≥ 60 years, experiencing joint pain, and being able to communicate verbally. Data collection was conducted through in-depth interviews, field notes, and audio recordings. Data analysis used the Colaizzi method. The results identified four main themes: (1) sensory perception and factors influencing the perception of joint pain, (2) efforts of the elderly in relieving pain through pharmacological and non-pharmacological strategies, (3) emotional reactions and efforts to achieve self-calming when pain occurs, and (4) the need for care and family support in pain management. The conclusion shows that self-management of joint pain in the elderly is influenced by individual understanding, emotional conditions, physical abilities, and family support. Continuous health education is essential to improve the elderly’s understanding of how to perform warm compresses independently, select safe medications according to medical recommendations, and apply relaxation techniques to maintain emotional stability when pain occurs. Active family involvement is also needed to enhance the effectiveness of joint pain self-management among the elderly.